Association between WASH Related Risk Factors and Stunting Among 6-24 Month Children at Puyung Health Center - Ramadhania, Yasmin Najla; Nurbaiti, Lina; Hasby, Amelia Ramdani (Jurnal Biologi Tropis, 2025)
A condition known as stunting happens when linear development falls short of its full potential, especially if it happens within the first 1000 days of life. Stunting prevalence in Indonesia was 21.5% in 2023, with a rate of 17.5% in Lombok Tengah District, West Nusa Tenggara Province. This study explores the relationship between WASH-related risk factors and stunting among children 6-24 months in Puyung Health Center area, Lombok Tengah District. This study is an observasional analytical research with a cross-sectional design. The research subjects included of 90 mothers or caregivers of children aged 6-24 month in Puyung Health Center are, Lombok Tengah Disctrict. Sampling was conducted through stratified random sampling. Data were collected using the KIA and a modified SSGI questionnaire 2022. The chi-square test was used for a bivariate data analysis. According to the statistical analysis of 90 respondents, 46 respondents (51.1%) were categorized as having no WASH-related hazards, while 49 infants (54.5%) suffered from stunting. A p-value of 0.821 (p>0.05) was achieved following a bivariate analysis using the chi-square test. These findings suggest that the prevalence of stunting in babies aged 6 to 24 months and in the Puyung Health Center region of the Central Lombok District do not significantly correlate with WASH risk factors. In the Puyung Health Center region of the Central Lombok District, there is no discernible link between stunting and WASH risk factors in children aged 6 to 24 months.